ABCD2 score and secondary stroke prevention. (28th July 2015) - Wardlaw, Joanna M.; Brazzelli, Miriam; Chappell, Francesca M.; Miranda, Hector; Shuler, Kirsten; Sandercock, Peter A.G.; Dennis, Martin S.
<x xml:space="preserve">Abstract</x> Objective: Patients with TIA have high risk of recurrent stroke and require rapid assessment and treatment. The ABCD2 clinical risk prediction score is recommended for patient triage by stroke risk, but its ability to stratify by known risk factors and effect on clinic workload are unknown. Methods: We performed a systematic review and meta-analysis of all studies published between January 2005 and September 2014 that reported proportions of true TIA/minor stroke or mimics, risk factors, and recurrent stroke rates, dichotomized to ABCD2 score </≥4. We calculated the effect per 1, 000 patients triaged on stroke prevention services. Results: Twenty-nine studies, 13, 766 TIA patients (range 69–1, 679), were relevant: 48% calculated the ABCD2 score retrospectively; few reported on the ABCD2 score's ability to identify TIA mimics or use by nonspecialists. Meta-analysis showed that ABCD2 ≥4 was sensitive (86.7%, 95% confidence interval [CI] 81.4%–90.7%) but not specific (35.4%, 95% CI 33.3%–37.6%) for recurrent stroke within 7 days. Additionally, 20% of patients with ABCD2 <4 had >50% carotid stenosis or atrial fibrillation (AF); 35%–41% of TIA mimics, and 66% of true TIAs, had ABCD2 score ≥4. Among 1, 000 patients attending stroke prevention services, including the 45% with mimics, 52% of patients would have an ABCD2 score ≥4. Conclusion: The ABCD2 score does not reliably discriminate those at low and high risk of early recurrent stroke, identify patients with carotid stenosis or AF needing urgent intervention, or streamline clinic workload. Stroke prevention services need adequate capacity for prompt specialist clinical assessment of all suspected TIA patients for correct patient management.